SPLENIC SIZE RELATION TO THE PORTAL VEIN DOPPLER ANALYSIS IN SUDANESE LIVER TRANSPLANTS - Mohammed Osman, Ashraf Mustafa; Gar al naby, Mohammed Al Fadil; Ahmed, Maha Esmeal; Awad alla, Babiker Abd Elwahab (International Journal of Research -GRANTHAALAYAH, 2019)
The purpose of this study was to identify the specific Doppler criteria for the portal vein as well as the spleen length or volume in liver transplants. A relative study was done after performing venous Doppler sonographic studies in 45 liver transplant cases (4 whole liver, 41 lobar) with no known vascular complications. The ultrasonic Doppler study were targeted to the portal vein flow direction, flow velocity in Doppler level and the caliber in gray scale level. Average gray scale and color flow mapping appearances as well as normal monophasic wave character was found. The following Doppler parameters were evaluated: for the portal veins, venous pulsatility index. There were no cases of portal vein obstruction found in our sample (neither stenosis, nor occlusion). Mean portal vein velocity was (less than 55 cm /s), the splenic length was (13.7±1.5). The relation between the portal venous index, and the splenic length was built. Both are useful parameters for diagnosing liver transplants complications.